ANALISIS PEMBERDAYAAN MASYARAKAT MELALUI BALAI EKONOMI DESA (BALKONDES) KARANGREJO KECAMATAN BOROBUDUR KABUPATEN MAGELANG - Larasati, Ajeng Diah; Nurcahyanto, Herbasuki; Marom, Aufarul (Journal of Public Policy and Management Review, 2024)
Community empowerment through Balkondes Karangrejo is the programs of Ministry of BUMN that uses CSR funds in the context of local economic development by utilizing the potentials that exist in the village environment. The Karangrejo Village community has received benefits from the existence of Balkondes Karangrejo, including an increase in income through PADes, the appointment of local potential, and the construction of facilities and infrastructure. The purpose of this research is to analyze the stages of community empowerment as well as the driving and inhibiting factors in the implementation of community empowerment through Balkondes Karangrejo. This research uses a descriptive method with a qualitative approach. The site of this research is Karangrejo Village which is located in Borobudur District, Magelang Regency. Data collection techniques in this study were through in-depth interviews, observation, and documentation. The results of the research are seen from the three stages of community empowerment, namely the stages of awareness, capacity building, and empowerment at Balkondes Karangrejo have not run optimally as evidenced by the obstacles still found at each stage of community empowerment. The driving factors of community empowerment through Balkondes Karangrejo are motivation and government policies, while the inhibiting factors of community empowerment through Balkondes Karangrejo are resources and availability of infrastructure and access.